Teaching of the Nursing Process in Brazil: literature review from 1996 to 2006 - Cogo, Ana Luísa; Pedro, Eva; Almeida, Miriam (Online Brazilian Journal of Nursing, 2006)
The present is a literature review aimed at identifying knowledge production on teaching of the nursing process in graduation courses in Brazil in the past decade. From May 1996 to May 2006, a systematized literature review was conducted using LILACS and MEDLINE databases and by means of a direct search of papers. Fourteen papers were selected predominantly quantitative descriptive exploratory researches (57.14%) carried out with teachers of nursing undergraduate courses (35.72%) or with nursing students (28.57%); the papers approached the topics of physical exam (35.71%) and nursing diagnosis (35.71%). Students considered the nursing process as important for the quality of nursing care; this requires teachers to develop the necessary skills and competences for its use. Among the most effective teaching strategies in the nursing process, the theoretical-practical activities are to be highlighted. Research suggesting practices and actions in the teaching of the different steps of the nursing process should be developed.